Correlation between Schizas Score, Degree of Disability, and Neurogenic Claudication in Lumbar Spinal Stenosis - Prasetya, Arief Indra Perdana; Gardjito, Fajar Baskoro; Prijosedjati, R. Andhi; Utomo, Pamudji; Handojo, Handry Tri (Indonesian Journal of Medicine, 2019)
Background: Magnetic Ressonance Imaging (MRI) is one of modality to diagnosed lumbar spinal stenosis (LSS) however there were some mismatch between the degree of canal stenosis to functional score of LSS. There are some methods to measure the degree of canal stenosis, on of them is Schizas Score. To asses functional score of patients with LSS, there are some tools can be used. Oswesstry Disability Index (ODI) and Neurogenic Claudication Outcome Score (NCOS) are questionnaire commonly used in LSS. This study aimed to analyze the correlation between the degree of stenosis grading using Schizas Score to the degree of disability using ODI score and Neurogenic Claudication using NCOS.Subjects and Method: This was an analytic observational study conducted at Prof. Dr. R. Soeharso Orthopaedic Hospital, Surakarta, Central Java. A sample of 35 patients with LSS in were assessed by filling ODI and NCOS questionnaire, then evaluate the lumbar axial MRI to identify the Schizas Score. The data were analyzed by Spearman test.Results: There was a significant correlation between Schizas Score to ODI score and NCOS. Schizas score increased ODI score (r= 0.91; p<0.001). Schizas score decreased NCOS (r= -0.90; p<0.001).Conclusion: Schizas score is correlated with ODI score and NCOS.Keywords: lumbar spinal stenosis, Schizas score, ODI, NCOSCorrespondence: Arief Indra Perdana Prasetya. Resident of Orthopaedic and Traumatology Specialist Program, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: absolutellydarkknight@gmail.com.Indonesian Journal of Medicine (2019), 4(2): 116-121https://doi.org/10.26911/theijmed.2019.04.02.05